High-adaptive sort of soy Aquamarine - Білявська, Л. Г.; Васецький, Ю. П.; Пилипенко, О. В.; Білявський, Ю. В.; Діянова, А. О. (Scientific Progress & Innovations, 2018)
The value of protein culture of soy, the universality of its use is shown. The ways of increasing soy production in Ukraine are considered. To the State Register of plant varieties, suitable for distribution, a significant number of various soybean varieties are listed in Ukraine, most of which have a narrow ecological-geographical adaptation. In modern conditions, the soybean must be highly productive, adaptive, with a high level of resistance to biotic and abiotic environmental factors. Based on long-term practical experience in soybean selection, the hybridization of sources of adaptability to stress factors of the environment resulted in a variety with a higher base potential. Aquamarine variety, entered in the State Register of plant varieties, is suitable for distribution in Ukraine. The morphological and biological characteristics of the variety are given.